2016
DOI: 10.1177/1082013216654414
|View full text |Cite
|
Sign up to set email alerts
|

Continuous microwave pasteurization of a vegetable smoothie improves its physical quality and hinders detrimental enzyme activity

Abstract: Graphic abstract AbstractThe effect of a pasteurization treatment at 90 ± 2 ºC for 35 s, provided by continuous microwave (MW) under different doses (low power/long time and high power/short time) or conventional pasteurization (CP) on the quality of orange-colored smoothies and their changes throughout 45 days of storage at 5 °C were investigated. A better color retention of the MW pasteurization (MWP) treated smoothie using high power/short time than in conventionally-processed sample was evidenced by the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 30 publications
3
23
0
4
Order By: Relevance
“…Benlloch-Tinoco et al (2015) studied the impact of MW (1000 W/340 s) and conventional pasteurization on the shelf life of a kiwifruit puree and observed a higher preservation of bioactive compounds (57-67%) in MW-treated samples regarding conventional pasteurization. In addition, Arjmandi et al (2016) reported a better color retention of an orange-colored smoothie after an alternative pasteurization treatment provided by MW at 90 ± 2°C for 35 s. Similar results were reported by Guzmán et al (2002), who observed a greener color in avocado puree treated with MW power density for a shorter time (31.65 W/g, 30 s).…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Benlloch-Tinoco et al (2015) studied the impact of MW (1000 W/340 s) and conventional pasteurization on the shelf life of a kiwifruit puree and observed a higher preservation of bioactive compounds (57-67%) in MW-treated samples regarding conventional pasteurization. In addition, Arjmandi et al (2016) reported a better color retention of an orange-colored smoothie after an alternative pasteurization treatment provided by MW at 90 ± 2°C for 35 s. Similar results were reported by Guzmán et al (2002), who observed a greener color in avocado puree treated with MW power density for a shorter time (31.65 W/g, 30 s).…”
Section: Introductionsupporting
confidence: 80%
“…Then, pesto sauce samples (approximately 1 kg) were heated in the same blender for conventional pasteurization (CP) at 85 ± 2°C during 5 min while samples (approximately 1 kg) for microwave treatment (MW) were packed in polyethylene bags embossed (100 g) and treated for 30 s/11 kW in an innovative semi-industrial prototype of a continuous microwave oven (SI-MAQ0101, Sairem Ibérica SL, Barcelona, Spain) which was previously described (Arjmandi et al 2016;Castillejo et al 2017). Briefly, the microwave oven consisted of four adjustable magnetrons (0.5-3.0 kW; 2450 MHz), a polytetrafluoroethylene (PTFE) feed belt able to work on continuous or back-andforth movement mode (semi-continuous), an optimized heating chamber, new energy economizing filters, a computer interface, and a fiber optic slip ring for online temperature measurements inside the microwave oven.…”
Section: Treatments and Storage Conditionsmentioning
confidence: 99%
“…The glasses were placed in the feed system of the MW oven and treated under low power/long time (210 and 260 W for 646 and 608 s) and high power/ short time (1600 and 3600 W for 206 and 93 s). Those power/time combinations of MWP were selected according to preliminary studies (Arjmandi et al 2016). For CP, samples (600 mL) were heated in the thermomix.…”
Section: Treatmentsmentioning
confidence: 99%
“…Continuous microwave pasteurization of a vegetable smoothie improves its physical quality and hinders detrimental enzyme activity. A better color retention of the microwave pasteurization-treated smoothie using high power/short time than in conventionally processed sample was evidenced by the stability of the hue angle Lower residual enzyme activities from peroxidase, pectin methylesterase and polygalacturonase were obtained undermicrowave heating, specifically due to the use of higher power/shorter time 97 . Delaying harvest time coupled with periods of heavy rainfall caused sprouting in the wheat kernels, observed as a drop in Falling Number and an increase in α-amylase activity.…”
Section: Introductionmentioning
confidence: 97%